2017
DOI: 10.1155/2017/8325049
|View full text |Cite
|
Sign up to set email alerts
|

Extract from Periostracum cicadae Inhibits Oxidative Stress and Inflammation Induced by Ultraviolet B Irradiation on HaCaT Keratinocytes

Abstract: Periostracum cicadae is widely used for the treatment of skin diseases such as eczema, pruritus, and itching. The current study sought to evaluate the effect of P. cicadae extract on ultraviolet B (UVB) irradiation and identify the mechanisms involved. Photodamage-protective activity of P. cicadae extracts against oxidative challenge was screened using HaCaT keratinocytes. P. cicadae extracts did not affect cell viability but decreased reactive oxygen species (ROS) production. The extract attenuates the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…A previous publication has reported that Nrf2 regulates numerous skin barrier structural and functional components and consequently plays an important role in skin barrier function [32]. It was reported that the activation of Nrf2 is a promising target of photoprotective supplements including bixin [32], tanshinone I [53], Lycium barbarum polysaccharide [54], Periostracum cicadae [55], zerumbone [56], and gremlin [57]. Since hydrangenol was described in a previous study as reducing ROS in UVB-irradiated Hs68 cells [27] and inhibiting pro-inflammatory mediators by activating Nrf2-mediated HO-1 signaling in lipopolysaccharide-induced BV2 microglial cells [25], to validate this phenomenon in vivo, we studied the inductive effects of hydrangenol on Nrf2 and the expression of Nrf2/ARE-dependent genes in the UVB-irradiated HR-1 hairless mice.…”
Section: Discussionmentioning
confidence: 99%
“…A previous publication has reported that Nrf2 regulates numerous skin barrier structural and functional components and consequently plays an important role in skin barrier function [32]. It was reported that the activation of Nrf2 is a promising target of photoprotective supplements including bixin [32], tanshinone I [53], Lycium barbarum polysaccharide [54], Periostracum cicadae [55], zerumbone [56], and gremlin [57]. Since hydrangenol was described in a previous study as reducing ROS in UVB-irradiated Hs68 cells [27] and inhibiting pro-inflammatory mediators by activating Nrf2-mediated HO-1 signaling in lipopolysaccharide-induced BV2 microglial cells [25], to validate this phenomenon in vivo, we studied the inductive effects of hydrangenol on Nrf2 and the expression of Nrf2/ARE-dependent genes in the UVB-irradiated HR-1 hairless mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results also showed that D. dasycarpus reduced inflammation activity via down-regulation of the p38 and JNK pathways, which could subsequently decrease IL-6 production [ 34 ]. D. dasycarpus displayed better anti-inflammatory bioactivity than the same concentration of P. cicadae upon oxazolone-stimulated in in vivo and in vitro models [ 19 ]. Hence, we propose that D. dasycarpus could be an antioxidant for therapy against skin exposure to oxazolone ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The herbs were purchased from Sun Ten Pharmaceutical Co., Ltd. (New Taipei City, Taiwan). Periostracum cicadae (PC) and D. dasycarpus (DD) were extracted with 50% v / v ethanol as previously reported [ 19 ]. All dried extract was weighed and re-constituted in 0.1% dimethyl sulfoxide (DMSO) containing culture medium to 1 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Extrinsic factors, such as solar radiation, induce the production of reactive oxygen species (ROS). ROS affect keratinocytes, which in turn secrete pro-inflammatory cytokines and produce more ROS [ 6 ]. Inflammation and oxidative stress also cause the production and activation of matrix metalloproteinases (MMPs).…”
Section: Introductionmentioning
confidence: 99%